ANALISIS KESULITAN MAHASISWA DALAM MEMAHAMI KONSEP VEKTOR GAYA PADA HUKUM NEWTON - Handhika, Jeffry; Kurniadi, Erawan (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
Vector is an important subject in physics. Application of Newtons laws will be difficult, if not understand the basic concept of vectors. At the time of completing the equation of Newtons laws, students have difficulty in identifying problems, more specifically students can not understand the concept vectors correctly. Based on the results of the analysis of errors made, from six students, only one student who answered correctly. Student errors are caused by the use of language dominance intuition and do not understand the concept of a vector.Keywords: Vector Concept, Newtons laws